2019
DOI: 10.3390/ijms20215367
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cholinergic Activity in the Hippocampus of Hippocampal Cholinergic Neurostimulating Peptide Precursor Protein Knockout Mice

Abstract: The cholinergic efferent network from the medial septal nucleus to the hippocampus has an important role in learning and memory processes. This cholinergic projection can generate theta oscillations in the hippocampus to efficiently encode novel information. Hippocampal cholinergic neurostimulating peptide (HCNP) induces acetylcholine synthesis in medial septal nuclei. HCNP is processed from the N-terminal region of a 186 amino acid, 21 kD HCNP precursor protein called HCNP-pp (also known as Raf kinase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 51 publications
7
25
0
Order By: Relevance
“…We demonstrated that HCNP-pp KO mice show diminished cholinergic projection to CA1. Additionally, the theta activity in CA1 of the hippocampus was reduced in HCNP-pp KO mice 18 . This electrophysiological data suggest that HCNP and/or HCNP-pp is involved in generation of theta oscillations in the hippocampus, which entrains the theta oscillation of the MSN via enhanced ACh release in the medial septum and the enhanced release of ACh in the CA1 stratum oriens 19 , 20 .…”
Section: Introductionmentioning
confidence: 95%
“…We demonstrated that HCNP-pp KO mice show diminished cholinergic projection to CA1. Additionally, the theta activity in CA1 of the hippocampus was reduced in HCNP-pp KO mice 18 . This electrophysiological data suggest that HCNP and/or HCNP-pp is involved in generation of theta oscillations in the hippocampus, which entrains the theta oscillation of the MSN via enhanced ACh release in the medial septum and the enhanced release of ACh in the CA1 stratum oriens 19 , 20 .…”
Section: Introductionmentioning
confidence: 95%
“…[ 4 ] On the other hand, conditional HCNP-pp knockout mice using Cre-ERT/loxP system by CaMKII-Cre transgenic mice revealed reduced power of theta rhythms in CA1 regions, whereas those mice showed no significant behavioral abnormality in locomotor, anxiety, or cognitive function. [ 13 ] In this model, downregulation of HCNP-pp expressions was possibly limited in cells controlled by CaMKII promoter, a hippocampal excitatory neuronal expression regulator, while HCNP-pp expressions are known to exist in inhibitory neurons, oligodendroglia, and hippocampal pyramidal neurons. [ 14 15 ] Further investigations are needed to provide a plausible explanation for HCNP function, including HCNP-pp downregulation in other kinds of cells by using Cre-transgenic mice driven other promotors.…”
Section: Hippocampal Cholinergic Neurostimulating Peptide-pp Genetic Modelsmentioning
confidence: 99%
“…HCNP in 14-day-old postnatal hippocampi[ 9 ] was initially isolated and later exhibited nerve- and fibroblast-like abilities, which enhanced cell growth. [ 16 17 ] Cholinergic axon terminals also decreased in stratum oriens of mice with inadequate HCNP-pp levels,[ 13 ] suggesting ChAT regulatory abilities of HCNP in septal cholinergic neuronal cells. Furthermore, HCNP in the hippocampus was found to be correlated to theta activity.…”
Section: Hippocampal Cholinergic Neurostimulating Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…The amino terminal of RKIP can be cleaved by sulfhydryl-containing chymotrypsin into a polypeptide of 11 amino acid residues, namely hippocampal cholinergic neurostimulating peptide (HCNP). HCNP can activate choline acetyltransferase in the central nervous system, promote the synthesis of acetylcholine, and then act on the cholinergic neuroreceptor system (10). In vitro experiments have shown that HCNP promotes insulin secretion, but it is not clear whether this effect passes through the cholinergic nervous system.…”
Section: Introductionmentioning
confidence: 99%